20th volume of Green Chemistry. Issue 1 (20th December 2017) - Jessop, Philip; Simpson, Anna
Abstract : Chair of the Editorial Board Philip Jessop and Executive Editor Anna Simpson reflect and look to the future as Green Chemistry begins its 20 th volume.